If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6x + 2 = -4x Reorder the terms: 2 + 3x + 6x = -4x Combine like terms: 3x + 6x = 9x 2 + 9x = -4x Solving 2 + 9x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 2 + 9x + 4x = -4x + 4x Combine like terms: 9x + 4x = 13x 2 + 13x = -4x + 4x Combine like terms: -4x + 4x = 0 2 + 13x = 0 Add '-2' to each side of the equation. 2 + -2 + 13x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 13x = 0 + -2 13x = 0 + -2 Combine like terms: 0 + -2 = -2 13x = -2 Divide each side by '13'. x = -0.1538461538 Simplifying x = -0.1538461538
| 10+10x=50+2x | | 8+w-4.7w-.5= | | 15x^2+26x+7= | | 125x^6-8=equation | | -4/9x=8 | | 5/√5xy^2 | | 5/√(5xy^2 | | 0=x^2+x-8 | | 80p^2r-245b^2r=0 | | 2v^2-10+12=0 | | 16v^4y^5-4v/4v^3x^6 | | 2r=7(r-15) | | 6m+3(2m-1)=-27 | | 5lnx-4=7 | | -9+20x=16 | | 5=-10n | | r=7r-52.5 | | 3a-(2-9b)= | | 50/950 | | 2m+(9m^2+3m)= | | 3x-17=-17+9x | | 7y-24=-15+6y | | 24y+2x=114 | | 4*x-1=X-2 | | 2(3+3x)-7=17 | | 20x-11-14x=3(2x-5)+4 | | t(t-1)=0 | | 0.5x+5=12.5 | | 4x(4+3y)-9(x+2xy)= | | 5(0.5x+2)=22.5 | | 22.5=10+2.5x | | 35.123/100 |